Information literacy research trend in Malawi: a guide for future research - Banda, Newton; Mwabungulu, Elias (University of Dar es Salaam Library Journal, 2020)
Research on information literacy skills (IL) that people of a particular area needs or lack is important in informing quality IL programs. Moreover, creating a collective understanding on IL research is important in guiding researchers towards gaps they have to address. This study has attempted to do that by reviewing IL research that has been conducted in Malawi for a period of 10 years starting from 2008. The study has purposively selected 18 studies that have met requirements for inclusion. Following the analysis, the study has established that majority of IL research has been carried out at institutions of higher learning. The study has also revealed lack of focus on some categories of literacy. A number of IL challenges have also been reported in the studies reviewed. Based on the findings, the study finds it imperative for information science researchers in the country to conduct more IL studies so as to address the current problem of limited studies. The study also finds the need for libraries and information providers to come up with a research agenda that will take researchers' focus to IL imperative.